2022
DOI: 10.7759/cureus.30145
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Interstitial Lung Disease in Rheumatoid Arthritis Patients: A Hospital-Based Study

Abstract: Introduction: Among various extra-articular manifestations of rheumatoid arthritis (RA), interstitial lung disease (ILD) is the most frequent and concerning manifestation. The reported frequency of RA-associated ILD (RA-ILD) varies in the literature. The objective of the present study was to determine the frequency of ILD in RA patients at a teaching hospital in Rawalpindi.Methods: 175 male and female patients between 18-70 years were enrolled in the study from January 21, 2022, till July 24, 2022. Patients di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The most common imaging pattern observed in RA-ILD patients was UIP, followed by nonspecific interstitial pneumonia (NSIP) ( 23 , 24 ). However, the classification methods for pILD and ILD varied among studies, making it difficult to determine the exact proportion of each imaging pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The most common imaging pattern observed in RA-ILD patients was UIP, followed by nonspecific interstitial pneumonia (NSIP) ( 23 , 24 ). However, the classification methods for pILD and ILD varied among studies, making it difficult to determine the exact proportion of each imaging pattern.…”
Section: Discussionmentioning
confidence: 99%
“…However, Olson et al reported that RA-ILD-associated mortality rates decreased in men but increased in women between 1988 and 2004 [8]. It was observed that RA incidence was predominant in females as opposed to males, with a male-to-female ratio of 1:3.1 [57]. Female sex was also an independent risk factor for the development of RA-ILD in a multi-ethnic Malaysian cohort study [58].…”
Section: Sexmentioning
confidence: 99%